Analisis Penerapan Akuntansi Lingkungan Berbasis Maqashid Syariah pada RSUD dr Fauziah Bireuen - Azhar Azhar; Dahlifah Dahlifah (Jurnal Edukasi (Ekonomi, Pendidikan dan Akuntansi), 2026)
This study aims to evaluate and analyze the implementation of Maqashid Shariah-based environmental accounting at dr. Fauziah Regional General Hospital. As a government hospital in a region implementing Islamic Sharia, environmental impact management is not only a regulatory obligation but also a spiritual responsibility. This study uses a qualitative method with a descriptive approach through in-depth interviews, observation, and documentation. The results show that dr. Fauziah Bireuen Hospital has operationally implemented medical waste management in accordance with standard operating procedures (SOP) and government regulations. However, administratively and financially, the hospital has not explicitly implemented environmental accounting in its financial reports. Environmental costs are still merged into general operational or overhead costs, so environmental cost transparency for stakeholders is not yet optimal. Viewed from the Maqashid Shariah perspective, the application of Islamic values has been partially internalized. This is reflected through the principles of Hifz al-Din (providing clean worship facilities), Hifz al-Nafs (protecting health through waste management), Hifz al-Aql (environmental management socialization), Hifz al-Nasl (preserving the ecosystem for future generations), and Hifz al-Mal (budget allocation, although not yet specifically transparent). This study recommends the need for a formal internal policy to separate environmental cost recording to increase accountability and public benefit.